Financial Distress Analysis of Retail Companies on IDX: Altman, Springate, and Zmijewski Models - Dayegha Feruziarya Putri Abelgissabella; Taufik Akbar (Universitas Hamzanwadi, 2025)
The Indonesian retail sector has experienced digital disruption and shifting consumer preferences, making early detection of financial distress increasingly important. This study aims to compare financial distress predictions of retail companies listed on the Indonesia Stock Exchange (IDX) using the Altman Z-Score, Springate, and Zmijewski models for the 2021–2024 period. A quantitative descriptive method was applied using secondary data from audited annual reports of 26 retail companies selected through purposive sampling. Financial ratios were calculated based on each model and classified to assess bankruptcy risk. The findings show that most companies fall into the safe zone across the three models, indicating generally strong liquidity, profitability, and solvency. However, several firms, particularly GLOB, TELE, and TRIO, are consistently categorized as distress, reflecting structural financial weaknesses and a high probability of bankruptcy without corrective action. The results highlight the role of multiple prediction models to enhance early warning accuracy and support managerial and investment decisions.